Analyzing the interaction of artificial intelligence and the formation of architectural design ideas - Negar Zargaran khoozany; Leila Zare (طراحی و برنامه ریزی در معماری و شهرسازی)
This article examines the very important and effective role of artificial intelligence in the process of forming design ideas in the field of architecture. In this review, the concept of idea, its importance in architectural design, and the applications of artificial intelligence in the evolution of the architectural design process are examined, and then some old and famous buildings designed by prominent architects with the help of artificial intelligence tools are examined. Design ideas refer to a set of principles, concepts and inspirations that help designers to create unique and attractive products, spaces and visual and user experiences. Another important issue is artificial intelligence, which is a branch of computer science that deals with the design and development of systems that are capable of performing human tasks. Artificial intelligence is undoubtedly one of the most dynamic and challenging fields of technology in today's world and will have a wide impact on the daily life and future of mankind. This study was conducted in a qualitative-analytical way and shows that artificial intelligence as a powerful tool is able to help architects to achieve more innovative and better design ideas. In the process of analyzing and proving this, artificial intelligence was asked to redesign landmark buildings according to the thoughts and theories of the world's great architects. The results of this redesign showed that the use of this tool helps architects' ideation, and it was concluded that through big data analysis, machine learning algorithms, and other advanced technologies, artificial intelligence can improve the design process and enable architects. to achieve more creative and high-quality solutions. This article not only deals with technological developments in the field of architecture, but also emphasizes the effective connection between artificial intelligence and architects ideation.